The Importance in Providing Country of Origin Information on E-Commerce Platforms to Fulfill Consumer Rights in Indonesia - Ridwan, Muhammad; Rizky, Said Muhammad (Veteran Law Review, 2019)
One of the threats of using the e-commerce system in Indonesian business sectors are the lack of goods and/or services information provided in the e-commerce platform, especially the country of origin information. The general standard of information that should be provided to consumers includes price, quality, and other information that can help consumers decide what to buy according to their needs and the quality of goods. The purpose of this study is to identify the importance of country of origin information in e-commerce platform based on consumer’s view. We used juridical-empirical research to find out how the implementation of a regulation. The primary sources were collected by observation method to the e-commerce platforms and survey method to the e-commerce customers. Based on theories and results, we conclude that country of origin information is important and should be provided by the merchants in the e-commerce platform. Providing country of origin information in e-commerce platform may benefit consumers and also may benefit e-commerce providers and merchants. The government needs to issue a new regulation to make e-commerce providers obligated to provide country of origin information for all of the products that their merchant sold. We also suggest the e-commerce providers to voluntarily and consciously requiring merchants selling on the platform to include country of origin information.